Effect of Exercise on Cognitive Ability, Cardiovascular Fitness, and Quality of Life in Post-Stroke Patients: Systematic Review and Meta-Analysis - Maingu, Bertha Sylvester; Murti, Bhisma; Widyaningsih, Vitri (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Following a stroke, cognitive ability, and cardiovascular fitness decline, exerting a substantial influence on physical rehabilitation and overall quality of life. Stroke management encompasses a multidisciplinary approach, with emerging studies highlighting the role of exercise in enhancing cognitive ability and cardiovascular fitness post-stroke. This study aims to analyze the effects of exercise on cognitive ability, cardiovascular fitness, and quality of life in stroke survivors, shedding light on potential therapeutic benefits. Subject and Methods: The PICO Model eligibility criteria were employed to execute the article search including P= post-stroke patients; I= exercises C= standard care, O= cognitive ability OR cardiovascular fitness OR quality of life. The study extracted articles from PubMed and ScienceDirect databases, with keywords